2023
DOI: 10.1172/jci.insight.162436
|View full text |Cite
|
Sign up to set email alerts
|

The m6A methyltransferase METTL16 negatively regulates MCP1 expression in mesenchymal stem cells during monocyte recruitment

Abstract: Mesenchymal stem cells (MSCs) possess strong immunoregulatory functions, one aspect of which is recruiting monocytes from peripheral vessels to local tissue by secreting MCP1. However, the regulatory mechanisms of MCP1 secretion in MSCs are still unclear. Recently, N6-methyladenosine (m 6 A) modification was reported to be involved in the functional regulation of MSCs. In this study, we demonstrated that methyltransferase-like 16 (METTL16) negatively regulated MCP1 expression in MSCs through m 6 A modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Therefore, the downregulation of chemokine expression in MSCs induced by parasite antigens may facilitate the innate immune evasion of parasites. Additionally, certain chemokines, such as CCL2, have been implicated in regulating the recruitment of MSC-osteoprogenitor cells and protecting against apoptosis induced by the external environment ( Yao et al, 2021 ; Zhang et al, 2023 ). Thus, alterations in chemokine expression in MSCs can have multiple biological effects and are closely associated with lesion development.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the downregulation of chemokine expression in MSCs induced by parasite antigens may facilitate the innate immune evasion of parasites. Additionally, certain chemokines, such as CCL2, have been implicated in regulating the recruitment of MSC-osteoprogenitor cells and protecting against apoptosis induced by the external environment ( Yao et al, 2021 ; Zhang et al, 2023 ). Thus, alterations in chemokine expression in MSCs can have multiple biological effects and are closely associated with lesion development.…”
Section: Discussionmentioning
confidence: 99%
“…METTL16, as a newly identified methyltransferase, was only reported to install m 6 A modifications on a few noncoding RNAs and pre-mRNAs in majorities of studies before 2018, such as MAT2A, U6 snRNA, and MALAT1 (Brown et al, 2016;Shima et al, 2017;Warda et al, 2017) but a subsequent study revealed that METTL16 could promote the translation of more than 4000 mRNA transcripts (Su et al, 2022) which implied that it had multiple undiscovered functions. Thereafter, multiple studies concentrated on the physiological function of METTL16 and discovered that it regulated the m 6 A modification on different mRNAs (Guo et al, 2022;Zhang et al, 2022Zhang et al, , 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that MSCs can induce changes in chemokine expression and osteogenic activity in themselves and surrounding cells through EVs ( Dabrowska et al, 2021 ). Chemokine expression plays a crucial role in parasite immunity by recruiting multiple immune cells and is one of the main immunomodulatory mechanisms of MSCs ( Yao et al, 2021 ; Zhang et al, 2023 ). Furthermore, in vivo experiments have revealed that transplantation of MSCs can improve the prognosis of hydatid disease by mitigating tissue damage and modulating the immune response, underscoring the significance of MSCs in the parasite–host interaction ( Kian et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%